Voir l’espace et dire le temps : le grand écart du discours esthétique victorien - Laurent Bury (Sillages Critiques)
Victorian painting was characterized by its narrativity, which attracted the public’s enthusiasm, but also the critics’ wrath or praise. While Henry James was offended by the “historicizing” reading of art works, John Ruskin usually wanted to find what came before and after the scene represented by the artist. Many Victorian painters thus tried to reconcile those two apparently incompatible dimensions of time and space, through all sorts of devices, juxtaposing canvases in order to create a more or less chronological series, resorting to polyptichs, adding titles which suggested a more literary apprehension of their work, etc. And Victorian critics also tried to straddle the gap between the spatial action of looking at a painting and the temporal reaction of understanding its meaning.